Beautiful trauma : an explosion, an obsession, and a new lease on life - Fogg, Rebecca (Avery, an imprint of Penguin Random House, 2023)
"After a freak accident, a young woman must recover from trauma and find what will make her whole again. Warm, funny, and brutally honest about what it means to feel vulnerable, this is a story of trauma and recovery for our time"--